NEUROLINGUISTICS AS AN INTERDISCIPLINARY SCIENCE - Feruza Sherali qizi, Mannonova (IJBLE Scientific Publications Community Inc., 2021)
The article makes a certain contribution to Methodology, Neuro-linguistics, Classroom Management, Cognitive Linguistics, and Text Interpretation. For further investigation we can suggest the followings: cross-level competence on language learning in different types standards and distinguishing skills of language. According to this helpful investigation the state of congruence in neuro-linguistic programming is believed to help with language fluency, as it suggests that teaching non-verbal communication in conjunction with phonology and functional language produces better language learning results.